Influence of bisphosphonates on alveolar bone density: a histomorphometric analysis - Milton Santamaria Júnior; Ana Carolina Cuzzuol Fracalossi; Maria Fernanda Martins Ortiz Consolaro; Alberto Consolaro (Sociedade Brasileira de Pesquisa Odontológica, 2010)
This study is a histomorphometrical analysis of the influence of the bisphosphonate alendronate on alveolar bone density. Eighteen male Wistar rats were randomly assigned to a control group (n = 9) that received no medication and an experimental group (n = 9) that received oral alendronate (1 mg/kg) from birth until euthanization at 3 months of age. Semi-serial 4-µm-thick transverse sections were obtained from the region between the roots of the left maxillary first molar, stained with hematoxylin and eosin, and examined with a Zeiss Axioskop II optical microscope for histomorphometric analysis. The images were captured with a digital camera coupled with the microscope and connected to a computer, and were analyzed using Image J 1.34s image-analysis software. A 1,200-point grid was positioned onto each digitized image. The number of intersection points of grid lines in the bone tissue was counted. The ratio between the number of points in the bone tissue and the total number of points of the grid (1,200) was used to determine the bone density of the analyzed tissue. Data from the control and experimental groups were compared and analyzed statistically by the Student's t-test (p = 0.05). There was no statistically significant difference (p = 0.3754) in the alveolar bone density between the control and alendronate-treated animals. It may be concluded that the bisphosphonate alendronate did not alter the morphology of the alveolar bone, maintaining its structural tissue characteristics in healthy animals.